The Influence of Service Quality and Trust on Loyalty with Customer Satisfaction as An Intervening Variable - Muhammad Sukron; Mahfudz Mahfudz (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research intens to verify customer loyalty regarding the services provided by PT BPR BKK Jateng (Perseroda) Demak Branch Office. The independent variables used in this research are service quality and trust, the dependent variable is customer loyalty, and the intervening variable is customer satisfaction. The data used in this research is primary data originating from distributing research questionnaires. The population in this research was all 5,117 customers of PT BPR BKK Jateng Demak Branch. This research sample was limited to 110 respondents. This research uses Structural Equation Modeling (SEM) analysis techniques with the AMOS 24.0 analysis tool. The result that service quality has a positive and significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on loyalty, trust has a positive and significant effect on loyalty, customer satisfaction has a positive and significant effect on loyalty. This research shows that banking companies must have service quality and trust so that they can increase customer loyalty and satisfaction.